Dietary Fibers from Fruits and Vegetables and Their Health Benefits via Modulation of Gut Microbiota. Issue 5 (23rd August 2019) - Cui, Jiefen; Lian, Yunhe; Zhao, Chengying; Du, Hengjun; Han, Yanhui; Gao, Wei; Xiao, Hang; Zheng, Jinkai
Abstract: Dietary fibers (DFs) regulate host health through various mechanisms related to their dietary sources, specific physicochemical structures, fermentability, and physiological properties in the gut. Considering the numerous types and sources of DFs and their different physicochemical and physiological properties, it is challenging yet important to establish the key mechanisms for the beneficial health effects of DFs. In this review, the types and structures of DFs from different fruits and vegetables were summarized and the effects of different processing methods on DF properties were discussed. Moreover, the impacts of DFs on gut microbial ecology, host physiology, and health were described. Understanding the complex interaction between different DFs and gut microbiota is vital for personalized nutrition. It is also important to comprehend factors influencing gut microbiota and strategies to regulate the microbiota, thereby augmenting beneficial health responses. The exploration of molecular mechanism linking DFs, gut microbiota, and host physiology may allow for the identification of effective targets to fight against major chronic diseases.